Implementation of The Simple Additive Weighting Method in Solving Decision Making Problems - Abd. Rahman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
Decision making to determine prospective Bidikmisi scholarship recipients is based on various criteria and parameters. In the process, the evaluation of these criteria and parameters often results in various errors. For that we need a system that can eliminate these errors. Computerized-based system is a solution that can overcome these problems. The system can use a variety of methods and depending on each need. For the selection case for Bidikmisi scholarship recipients, the Simple Additive Weighting algorithm is suitable to be applied, considering that from several studies related to the application of this algorithm in supporting decision making, it turns out that it can provide a fast and accurate solution. It is hoped that the results of this research can later be implemented in the selection process for Bidikmisi scholarship recipients at IAIN Palopo so that a list of Bidikmisi scholarship recipients can be obtained quickly and accurately.